STRATEGI EFEKTIF MENGHADAPI TANTANGAN KOMUNIKASI ANTARBUDAYA DALAM LINGKUNGAN KERJA GLOBAL STUDI PADA PT GARUDA INDONESIA - Elma Tiana (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In the era of globalization, PT Garuda Indonesia faces challenges in intercultural communication in its global work environment. Differences in language, values, and communication styles can affect internal coordination and customer service. To address this, Garuda Indonesia implements strategies such as cross-cultural communication training, the use of international languages, and strengthening an organizational culture that values ​​diversity. These strategies have proven effective in preventing miscommunication and creating an inclusive and adaptive work culture. It is recommended that training be continuously updated, interactive communication spaces developed, and culturally sensitive leaders recruited to strengthen synergy and global competitiveness. With this approach, Garuda Indonesia can maintain professional performance and build a positive image in the international arena.